The Role of Oral Dissolution Therapy in Increasing the Efficacy of Extracorporeal Shockwave Lithotripsy in Patients with Less Than 2 Centimeters of Renal Stones: A Systematic Review - Mahaputra, I Komang Bintang Satria; Indradiputra, I Made Udiyana; Sanjaya, I Dewa Gede Reza (International Journal Labs, 2023)
The prevalence of renal stones is about 15% of the population. The trend is increasing with a high recurrence rate of up to 50% in 5 years, demanding a more sophisticated treatment for renal stones. ESWL is a treatment for less than 2 cm renal stones with good outcomes. Although ESWL is a technique with many advantages, many factors contribute to the outcome of ESWL with size and stones density as the most important factor. Oral dissolution therapy (ODT) has been used for decades and its effect on renal stones is beneficial to dissolve and prevent renal stones recurrence. The combination of ODT and ESWL is not yet recommended by current guidelines. The purpose of this systematic review is to summarize the latest evidence on the role of ODT in increasing the efficacy of ESWL for renal stones. The database used in this study are PubMed and Cochrane using keywords “urolithiasis”, “renal”, “shock wave”, “citrate”, and “oral dissolution therapy”. The outcome of the article sought is stone fragmentation after ESWL. 4 studies were included, and 3 compared the outcome between ESWL alone and ESWL combined with ODT. The outcome of combined therapy shows superior outcomes compared to ESWL alone with fewer sessions required for stone clearance or a higher chance for stone fragmentation. One study in children showed 100% stone clearance after ESWL with ODT, which was higher than the average success rate of ESWL in children with renal stones. Oral dissolution therapy may have a role in increasing the efficacy of extracorporeal shockwave lithotripsy for patients with less than 2 cm renal stones.